Processos de inovação tecnológica para a glicerina produzida no processo de obtenção de biodiesel no Brasil - Pinheiro, Rafael Sanaiotte (Universidade Federal de São Carlos, 2011)
Biodiesel is considered as a viable alternative to partially replace fossil fuels. The manufacture process of biodiesel produces approximately 10% glycerin, the main byproduct. Due to the growth of the biodiesel industry in Brazil and abroad, the high volumes of glycerin become a bottleneck in this chain, given that currently use the glycerin market serves a very narrow and specific. Many efforts have been directed to find strategic alternatives for the sustainable use of biodiesel derived glycerin. The competitiveness of the production chain, which originates with the glycerin byproduct of the manufacture of biodiesel, has as one of its determinants identifying technological routes and products to intensify the consumption of this product. In this dissertation, the goal was to determine how it is being done to manage technological innovation and progress in the identification and discussion of the influence which the glycerin is delivering on the biodiesel production chain, seeking possible ways to increase both competitiveness of Brazilian production chain glycerin and biodiesel. To achieve this, interviews were conducted with biodiesel producers, producers and consumers of glycerin and laboratories and research institutes. These interviews were conducted with the aid of a semi-structured questionnaire. A documentary analysis on patents involving the object of study was also performed to verify the main uses found for glycerin. With this, through a chain mapping of glycerol, was described and analyzed the dynamics of their operation and also identified the players who participate directly and indirectly, as well as the productive chains of biodiesel and glycerin are dealing with the management technological innovation aimed at the production thereof. By analyzing the factors of firm strategy, industry standard, technology transfer, leadership, opportunity, appropriability and cumulative, and also with the emergence of new businesses and new markets for the sector was possible to identify a great technological potential for the sector of glycerin. However, due to technological challenges still exist in the production process of biodiesel, this biofuel industry is not focused on these new opportunities.
Keywords: Cadeia agroindustrial; Gestão da inovação; Glicerina; Biodiesel; Agro-industrial chain; Management of technological innovation; Glycerin; Biodiesel; ENGENHARIAS::ENGENHARIA DE PRODUCAO